(untitled) (Quinto Sol, 2022)
At the National Convention held in the last days of 1934 and in the first days of 1935, the Unión Cívica Radical (Radical Civic Union) decided to return to electoral competition, after more than three years of abstaining. This article analyzes both the speeches that were delivered at the Convention and the framework in which it took place. Since the attitude to adopt in the face of a device (the electoral one) that was constitutive of radicalism was discussed there (the party had arisen in 1890 to demand free suffrage), we consider that the 1934-35 Convention constitutes a privileged setting to explore radical identity in the mid-1930s. The work takes as a source for the analysis the original minutes of the Convention, which provide the complete version (or, at least, the most complete available) of the speeches delivered in this party assembly that, for different reasons, had decisive consequences on the political evolution not only of radicalism, but of the country as a whole.